COMMUNICATION STYLES OF THE GUIDE IN ENGLISH AND UZBEK TOURIST SPEECH (International journal of artificial intelligence, 2025)
This study examines the communication styles of tour guides operating in English and Uzbek-speaking contexts, focusing on both verbal and non-verbal aspects. Tour guides are crucial facilitators of cultural exchange, providing tourists with insights into the history, culture, and attractions of their destinations. Effective communication by guides significantly enhances tourists' experiences, making this study particularly relevant in the context of global tourism. The research involved 20 tour guides, equally divided between English and Uzbek speakers, each with substantial experience in conducting tours. Data collection included direct observation, audio and video recordings of tours, and in-depth interviews with the guides. This comprehensive approach allowed for a detailed analysis of communication patterns, including speech, gestures, eye contact, and other forms of non-verbal communication. Verbal communication analysis revealed distinct differences between the two groups.